Large-scale multiferroic complex oxide epitaxy with magnetically switched polarization enabled by solution processing. Issue 1 (8th October 2019) - Liu, Cong; An, Feng; Gharavi, Paria S M; Lu, Qinwen; Zha, Junkun; Chen, Chao; Wang, Liming; Zhan, Xiaozhi; Xu, Zedong; Zhang, Yuan; Qu, Ke; Yao, Junxiang; et al.
Abstract: Complex oxides with tunable structures have many fascinating properties, though high-quality complex oxide epitaxy with precisely controlled composition is still out of reach. Here we have successfully developed solution-based single-crystalline epitaxy for multiferroic (1- x )BiTi(1- y )/2 Fe y Mg(1- y )/2 O3 –( x )CaTiO3 (BTFM–CTO) solid solution in large area, confirming its ferroelectricity at the atomic scale with strong spontaneous polarization. Careful compositional tuning leads to a bulk magnetization of 0.07 ± 0.035 μB /Fe at room temperature, enabling magnetically induced polarization switching exhibiting a large magnetoelectric coefficient of 2.7–3.0 × 10 −7  s/m. This work demonstrates the great potential of solution processing in large-scale complex oxide epitaxy and establishes novel room-temperature magnetoelectric coupling in epitaxial BTFM–CTO film, making it possible to explore a much wider space of composition, phase, and structure that can be easily scaled up for industrial applications.